Long telomeres bypass the requirement for telomere maintenance in human tumorigenesis - Taboski, Michael A. S. (2012)
Despite the importance of telomere maintenance in cancer cell survival via the elongation of telomeres by telomerase reverse transcriptase (TERT) or Alternative Lengthening of Telomeres (ALT), it had not been tested directly whether telomere maintenance is dispensable for human tumorigenesis. We engineered human tumor cells containing loxP-flanked hTERT to enable extensive telomere elongation prior to complete hTERT excision. Despite unabated telomere erosion, hTERT-excised cells formed tumors in mice and proliferated in vitro for up to one year. Telomerase reactivation or ALT was not observed, and the eventual loss of telomeric signal coincided with loss of tumorigenic potential and cell viability. Crisis was averted via the reintroduction of active but not inactive hTERT. Thus, telomere maintenance is dispensable for human tumorigenesis when telomere reserves are long. Yet, despite telomere instability and the presence of oncogenic RAS, human tumors remain susceptible to crisis induced by critically short telomeres.